Fuzzy Translations of A Fuzzy Set in UP-Algebras - Aiyared Iampan (IndoMS, 2017)
In this paper, we apply the concept of fuzzy translations of a fuzzy set to UP-algebras.For any fuzzy set μ in a UP-algebra,the concepts of fuzzy α-translations of μ of type I and of fuzzy β-translations of μ of type II are introduced, their basic properties are investigated and some useful examples are discussed.The concepts of prime fuzzy sets and of weakly prime fuzzy sets in UP-algebras are also studied.Moreover, we discuss the concepts of extensions and of intensions of a fuzzy set in UP-algebras.